2018
DOI: 10.1080/00140139.2018.1474267
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of economy and sagittal plane trunk movements among back-, back/front- and head-loading

Abstract: It has been suggested that freedom of movement in the trunk could influence load carriage economy. This study aimed to compare the economy and sagittal plane trunk movements associated with three load carriage methods that constrain posture differently. Eighteen females walked at 3 kmh with loads of 0, 3, 6, 9, 12, 15 and 20 kg carried on the back, back/front and head. Load carriage economy was assessed using the Extra Load Index (ELI). Change in sagittal plane trunk forward lean and trunk angle excursion from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…In loaded running, it has been shown that a front/back backpack design is more economic, especially after prolonged running (Scheer et al, 2020b). Postural sway and trunk movement from backpack usage may also negatively affect energy expenditure (Folland et al, 2017;Hudson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In loaded running, it has been shown that a front/back backpack design is more economic, especially after prolonged running (Scheer et al, 2020b). Postural sway and trunk movement from backpack usage may also negatively affect energy expenditure (Folland et al, 2017;Hudson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies generally examine loads that are heavier than those encountered in loaded running, as well as slower locomotion speeds, thus making the transfer of results to runners challenging or impossible (Knapik et al, 1996;Simpson et al, 2017). Studies on these populations showed that load position may influence energy expenditure (Lloyd and Cooke, 2000;Hudson et al, 2018), suggesting that load close to the center of mass may be the most effective way of carrying load, especially when walking (Knapik et al, 1996;Abe et al, 2004;Hudson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study only included a few different weights, which were not tailored to individual participants’ abilities; classification into, e.g., loads that are easy vs. difficult to lift for a specific participant may have resulted in very different results. The study also only included one frontal box position as opposed to, e.g., holding a box low or high in front of the body, and did not include any back load, commonly seen in other studies of carrying behavior [ 23 , 26 , 27 ]. All participants also walked at a self-selected walking speed, which may not have adequately captured differences between slow and fast gait.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, carrying behavior has been studied with wearable sensors in significantly less detail. While camera-based studies have shown significant differences between different load locations and weights [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ], to the best of our knowledge only four studies have attempted to automatically classify different load carriage types with wearable sensors, which would be the prerequisite for control of assistive devices. Benocci et al [ 29 ] used four IMUs and a k-nearest-neighbor classifier to differentiate among six backpack positions (all with the same weight): none, on both shoulders, on only left shoulder, on only right shoulder, in right hand, and in left hand; they achieved an overall classification accuracy of 96.7%.…”
Section: Introductionmentioning
confidence: 99%